Allotransplantation Effect of Fetoplacental Complex Cryopreserved Tissues on Endocrine Status of Men with Oligozoospermia - Grischenko, V. I.; Gerodes, A. G.; Keros, V. A.; Alipova, E. K.; Lutskaya, L. I.; Yurchenko, G. G. (Problems of Cryobiology and Cryomedicine, 2003)
There has been studied the effect of cryopreserved placental and fetotesticular tissue allotransplantation on the production of gonadotropic hormones and spermatogenesis in patients with oligozoospermia. Following fetoplacental tissue transplantation there was found a significant increase of testosterone level in blood serum, normalization of FSH and LH levels, as well as the change in the estradiol-testosterone ratio towards the androgen rise. When testing ejaculate there was noted a considerable augmentation of spermatozoa concentration, kinetic activity of those, fall of the amount of pathological forms. After the therapy performed all the patients noted libido increase, work efficiency rise, better feeling, fatigability reduction and cold disease rate. Application of cryopreserved fetoplacental tissue transplantation as a treatment method is of perspective in a combined therapy of sexual system pathologies in men.